Liability of legal entities under public law under the immunity of the foreign state that created them - Yu. M. Zhornokui (Bulletin of Kharkiv National University of Internal Affairs)
The article analyses current Ukrainian legislation, international conventions and doctrinal approaches to the issues of liability of public law legal entities under the immunity of the foreign State which created them. It is noted that by their legal nature, immunities as they exist in modern law are legal exceptions established by the State, since they are legal means aimed at regulating public relations. A characteristic feature of legal immunity is that it provides for additional rights or exemptions from obligations only in the area of legal liability.